Gravity flow vertical farming using aquaphonic system - Mohd Hafizuddin, Mokhtor (2013)
This research was focused on demonstrating that vertical farming is an alternative solution to reduce environmental problem and lack of healthy food problem. The objective of the study is to design and fabricate vertical farming aquaponic system for home application. The main part of this study is to rear Red tilapia, grow vegetable and strawberry plants. It is also a way to show a method to plant the vegetable and rear aquatic animal at a safe place without endangering the people but at the same time give benefit to the mother earth. This research involved designing and fabrication of aquaponic. The vegetable was planted inside the basket of the pipe holes while the fish was kept in the fish tank. The type of bed grow is used was a curved tank located above the fish tank. The water from the fish tanks will be pumped to the grow bed. The water filtered by plant then will flow back to the fish tank. The design of the piping system consist of six pipes and each with a diameter of 100 mm and have seven holes drilled at equidistance. The water flow rate is 1.2408 x 10-3 m3 /s from supply pump. There were also two curved tanks placed inside the aquaphonic house which used the floating polystyrenes planting system. The curved tanks are made of fiber glass that was fabricated and strengthened. A stress and strain analysis was done to the aquaphonic curve tank before and after reinforcement. As a result, the maximum displacement of the curve tank decreased after reinforcement process was done. The system was completed and installed.